1970
DOI: 10.3126/hjs.v5i7.1288
|View full text |Cite
|
Sign up to set email alerts
|

The Paleogene record of Himalayan erosion; Burma and Bangladesh

Abstract: DOI = 10.3126/hjs.v5i7.1288 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.94

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The Paleogene units of onshore delta of the Bengal basin are however still debatable, as they vary compositionally from being primarily quartzose nonorogenic [Uddin and Lundberg, 1998] to orogenic in character with meta-sedimentary lithic fragments [Johnson and Nur Alam, 1991;Najman et al, 2008]. A lower Neogene uplift of the Himalayas is confirmed along all segments of the Himalayas from west [e.g., Beck et al, 1995] through central [e.g., DeCelles et al, 2004] to the east [e.g., Uddin et al, 2007].…”
Section: Introductionmentioning
confidence: 86%
“…The Paleogene units of onshore delta of the Bengal basin are however still debatable, as they vary compositionally from being primarily quartzose nonorogenic [Uddin and Lundberg, 1998] to orogenic in character with meta-sedimentary lithic fragments [Johnson and Nur Alam, 1991;Najman et al, 2008]. A lower Neogene uplift of the Himalayas is confirmed along all segments of the Himalayas from west [e.g., Beck et al, 1995] through central [e.g., DeCelles et al, 2004] to the east [e.g., Uddin et al, 2007].…”
Section: Introductionmentioning
confidence: 86%
“…That, combined with paleocurrent data, indicates a Tethyan Himalayan source [ Qayyum et al , 2001]. Similarly, the deltaic, Oligo‐Miocene Barail Formation in Bangladesh has a Himalayan provenance, again with a notable Tethyan Himalayan component [ Najman et al , 2008a].…”
Section: Stratigraphy and Age Control In The Forelandmentioning
confidence: 99%
“…Evidence for increasing exhumation rates during the Oligocene comes from the sections preserved in the syntaxes. The thickness of both Khojak (∼6 km) and Barail (∼1 km) formations and the short lag times between mica cooling and sediment deposition in the Barail Formation suggest that the Himalayas had started to erode more rapidly in the Early Oligocene compared to the Eocene [ Najman et al , 2008a]. Zircon fission track and 40 Ar‐ 39 Ar ages in detrital grains of the Barail Formation also indicate that exhumation rates in the Himalaya began to increase after ∼40 Ma [ Najman et al , 2008a], as demonstrated by the increased proportion of detrital grains younger than 55 Ma (i.e., cooling ages younger than the onset of India‐Eurasia collision; Figure 3a).…”
Section: Correlation With Himalayan Exhumationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore interesting to have better knowledge of the composition of this mineral in a Large Igneous Province such as the Deccan Traps of western India, given that the age of this igneous event is slightly earlier to, or coeval with, the Cretaceous-Tertiary boundary. Moreover, materials rich in chromiferous spinels are widespread in the detritic successions of Arabian Sea and Bay of Bengal and may derive from dismantling the Deccan successions (Najman et al 2008).…”
Section: Introductionmentioning
confidence: 99%